Pelatihan dan Praktek Ilmu Tadwid Tingkat Dasar di SDN I Johowinong Mojoagung Jombang - Miftachul Chusnah; Mochammad Syafiuddin Shobirin; Fani Ardiansyah; Elyfia Qurrotu Ayunina; Intan Nur Roin Wijayanti (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2023)
Johowinong Village is located in the Mojoagung sub-district, Jombang Regency, most of the elementary school students in grades V and VI still do not know and understand the science of recitation and are not yet able to read the Al-Quran properly and correctly, that is why there needs to be a community service program carried out in Johowinong Village, Mojoagung. Jombang Regency to introduce and provide an understanding of basic level recitation knowledge to students at SDN I Johowinong, so that they are expected to be able to apply and be able to read the Qur'an well and correctly. This activity was held on September 6 2023 for class V and VI students at SDN I Johowinong. The method used in this community service activity is the Participatory Action Research (PAR) approach, which is a method of raising public awareness regarding potential and existing problems and encouraging community participation in the change activities that will be implemented. The stages of implementing the activities include: looking for existing problems in schools, compiling a pocket book on the science of tajwid which is applied in training and practicing the science of tajwid at the basic level. The next step was to distribute student understanding questionnaires regarding the science of recitation before carrying out training and practice of the science of recitation which was carried out in the hall of SDN Johowinong 1 and the final activity was distributing questionnaires after the training and practice of the science of recitation. Of the 70 students who filled out the questionnaire, it showed that 28% of students already knew and knew the science of recitation, while 72% of students did not master it. After this activity, it showed that the average score of "yes" had a percentage of 96% compared to the score of "no" which was only 4%. So it can be concluded that the training activities and practice of basic tajwid science can run smoothly and are well received. Keywords: Training, Practice, basic Tajwid knowledge